2011
DOI: 10.1056/nejmoa1008816
|View full text |Cite
|
Sign up to set email alerts
|

Irbesartan in Patients with Atrial Fibrillation

Abstract: Irbesartan did not reduce cardiovascular events in patients with atrial fibrillation. (Funded by Bristol-Myers Squibb and Sanofi-Aventis; ClinicalTrials.gov number, NCT00249795.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…In comparison, post‐hoc analyzes of randomized, controlled trials in patients with CHF but without known AF have suggested that RAS inhibition might reduce the incidence of new‐onset AF 33, 34, 35. In contrast, 2 prospective, randomized trials on patients with AF did not show beneficial effects of RAS inhibition with regard to future AF burden similar to our findings 36, 37. Explanatory mechanisms for the possible antiarrhythmic property of RAS inhibition, such as restrained electrical and structural remodeling, have been proposed in preclinical studies 7, 8, 9.…”
Section: Discussionsupporting
confidence: 85%
“…In comparison, post‐hoc analyzes of randomized, controlled trials in patients with CHF but without known AF have suggested that RAS inhibition might reduce the incidence of new‐onset AF 33, 34, 35. In contrast, 2 prospective, randomized trials on patients with AF did not show beneficial effects of RAS inhibition with regard to future AF burden similar to our findings 36, 37. Explanatory mechanisms for the possible antiarrhythmic property of RAS inhibition, such as restrained electrical and structural remodeling, have been proposed in preclinical studies 7, 8, 9.…”
Section: Discussionsupporting
confidence: 85%
“…The patient pool included those from two parallel trials: ACTIVE A and ACTIVE W. Irbesartan appeared to have limited benefit in the outcomes assessed by the Active I investigators; there was no change in risk of MI [83]. …”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Most of the current clinical data on upstream AF therapy are, however, derived from observational studies that were not sufficiently powered. Generally, while many clinical studies in the early - mid 2000 th were very promising, revealing a significant AF reduction with various upstream therapy agents (i.e., ACEIs, ARBs, statins, PUFAs) in a number of AF pathologies, results of the recent studies, particularly from large randomized clinical trials, have been quite sobering (Camm et al , 2010; Disertori et al , 2009; Yusuf et al , 2011; Kowey et al , 2010; Almroth et al , 2009; Schwartz et al , 2011; Bianconi et al , 2011; Savelieva et al , 2011a; Savelieva et al , 2011b). These later data indicate that PUFAs do not significantly affect the incidence of new onset AF and AF recurrence (Camm et al , 2010; Kowey et al , 2010; Bianconi et al , 2011; Savelieva et al , 2011a; Savelieva et al , 2011b).…”
Section: 0 Upstream Therapy Targets For Afmentioning
confidence: 99%
“…These later data indicate that PUFAs do not significantly affect the incidence of new onset AF and AF recurrence (Camm et al , 2010; Kowey et al , 2010; Bianconi et al , 2011; Savelieva et al , 2011a; Savelieva et al , 2011b). ACEIs and ARBs may indeed reduce new onset AF (i.e., primary prevention) but this positive effect is limited only to patients with significant systolic dysfunction and hypertension (Camm et al , 2010; Healey et al , 2005; Maggioni et al , 2009; Disertori et al , 2009; Yusuf et al , 2011; Ducharme et al , 2006). Reasonably proven anti-AF efficacy of statins is largely limited to the prevention of new-onset AF post-operatively (Savelieva et al , 2011a; Camm et al , 2010).…”
Section: 0 Upstream Therapy Targets For Afmentioning
confidence: 99%